Meta-Analysis the Effect of Hormonal Contraception on the Weight Gain and Hypertension in Women of Reproductive Age - Kusumaningtiyas, Zonna Aditiya; Tamtomo, Didik; Murti, Bhisma (Journal of Maternal and Child Health, 2022)
Background: Hormonal contraception is a contraceptive method that can prevent pregnancy because it contains estrogen and progesterone. The use of hormonal contraception for a long time can cause side effects including increased body weight, cholesterol deposits, and hypertension. The purpose of this study was to examine, analyze, and estimate the magnitude of the effect of the use of hormonal contraception on the incidence of weight gain and hypertension in women of childbearing age based on the results of previous similar studies. Subjects and Method: This study is a systematic review and meta-analysis using PRISMA flowchart diagrams. The process of searching for articles was carried out between 2004-2021 using 3 databases, including Google Scholar, PubMed, and Science Direct. The keywords used in the database search are ""Hormonal Contraception" AND “DPMA injection” AND "Weight Gain" AND "Hypertension". Inclusion criteria for full text articles used the observational Randomized Controlled Trial method, the articles used English, and reported the Mean and SD in multivariate analysis. Articles that met the requirements were analyzed using the RevMan 5.3 application. Results: A total of 14 articles with a Randomized Controlled Trial study design originating from Thailand, Indonesia, Pakistan, America, California, Africa, Ethiopia, and Kenya were meta-analyzed in this study. Meta-analysis of 7 articles showed that hormonal contraception had an effect on weight gain in women of childbearing age by 0.03 units but not statistically significant (SMD= 0.03; 95% CI= 0.07 to 0.14; p= 0.530). Meanwhile, 7 articles showed that hormonal contraception increased the incidence of hypertension in women of childbearing age by 0.10 units, but it was not statistically significant (SMD= 0.10; 95% CI= 0.17 to 1.37; p= 0.460). Conclusion: Hormonal contraception increases body weight and hypertension in women of childbearing age. Keywords: hormonal contraception, weight gain, hypertension, meta-analysis. Correspondence:Zonna Aditiya Kusumaningtiyas. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: zonnaaditiya22@gmail.com. Mobile: +6282234998054.